A Review of Catalytic Innovations in the Synthesis of 1, 4-Dihydropyrano [2, 3-C] Pyrazoles via Four Component Method in the Last Decade (International Journal of Scientific Research in Science and Technology, 2025)
1,4-Dihydro Pyrano [2,3-c]pyrazole (1,4-DHPP) derivatives have many biological and medicinal properties hence received an interest by organic and medicinal chemists. Now a days multi-component reactions (MCRs) have been adopted for the synthesis of highly functionalized 1,4-dihydro pyrano[2,3-c] pyrazole derivatives as MCRs have its own importance in the field of chemistry and environment. . This review gives detail information about the methods used to synthesize 1,4-Dihydro Pyrano [2,3-c]pyrazole derivatives by one-pot four components over the last ten years. As compared with two components and three component methods four component condensation method is used in the greater extent by the researchers. This review also gives information about the different catalytic techniques and methods use for the synthesis of 1,4-DHPP.